Optimum light intensity for larval rearing of brown marbled grouper Epinephelus fuscogttatus - Mukai, Yukinori (2011)
Brown-marbled grouper Epinephelus fuscogttatus hachted with immature sensory organs, however their sensory organs developed rapidly after hatching. Their eyes had only cone cells in their retinae until commencement of the methamorphosis. The brown-marbled grouper larvae got rod cells at 25-day-old, then, retinomotor responses occured in their retinae. The retinomotor responses occured between 0.1 lx and 1 lx. Feeding experiments showed that the larvae ingested Artemia with high ingestion rates in 10 lx and above. This study recommends the light intensities of 100 lx to 1000 lx for larval rearing of brown marbled grouper.